1996
DOI: 10.1016/s0735-1097(96)00268-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Cytokines and Their Endogenous Modulators in Patients With Mild to Severe Congestive Heart Failure Due to Coronary Artery Disease or Hypertension

Abstract: In patients with congestive heart failure, circulating levels of cytokines increased with the severity of symptoms. In these patients, circulating levels of sTNF-RII and IL-1-Ra are more sensitive markers of immune activation than are circulating levels of TNF-alpha and IL-1-beta, respectively. Levels of IL-2 and IL-2-sR are not elevated when congestive heart failure is due to coronary artery disease or hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
289
3
13

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(314 citation statements)
references
References 21 publications
9
289
3
13
Order By: Relevance
“…We also observed that Ang (1-7) treatment reduced the elevated levels of IL-1b, IL-6 and TNF-a expression in the failing myocardium. Several studies have shown that in both animals and humans with failing hearts, levels of inflammatory cytokines (e.g., IL-1b, IL-6 and TNF-a) are increased in the plasma 20,21 and in the circulating leukocytes, 22 as well as in the myocardium itself. [23][24][25] Our observation that the levels of IL-1b, IL-6 and TNF-a were elevated in the failing myocardium of mice, 12 weeks after 5/6 NC, is consistent with those of earlier findings.…”
Section: Angiotensin (1à7) Prevent Heart Dysfunction and Left Ventricmentioning
confidence: 99%
“…We also observed that Ang (1-7) treatment reduced the elevated levels of IL-1b, IL-6 and TNF-a expression in the failing myocardium. Several studies have shown that in both animals and humans with failing hearts, levels of inflammatory cytokines (e.g., IL-1b, IL-6 and TNF-a) are increased in the plasma 20,21 and in the circulating leukocytes, 22 as well as in the myocardium itself. [23][24][25] Our observation that the levels of IL-1b, IL-6 and TNF-a were elevated in the failing myocardium of mice, 12 weeks after 5/6 NC, is consistent with those of earlier findings.…”
Section: Angiotensin (1à7) Prevent Heart Dysfunction and Left Ventricmentioning
confidence: 99%
“…Plasma levels of angiotensin II, tumour necrosis factor-α (TNF-α), and interleukin-1β increase as symptoms worsen in patients with advanced HF [24]. Cytokines activate NAD(P)H oxidase, thereby increasing superoxide production [25][26][27].…”
Section: "Systemic Endothelitis" In Acute Heart Failurementioning
confidence: 99%
“…The aforementioned cytokines play a dual role, activating apoptosis in myocytes (13), while also functioning in a cytoprotective manner (15). Furthermore, inappropriate activation of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) have been recognized as an important mediator in the development of endothelial dysfunction, cardiac hypertrophy, and heart failure in experimental animal models and in humans (9,17,28,30). Atrial natriuretic peptide (ANP) has been shown to inhibit the TNF-α induced adhesion molecule expression in endothelial cells (32).…”
Section: Introductionmentioning
confidence: 99%